Reflexión sobre el papel del fonoaudiólogo en la salud oral - Barreto, Miryan A. (Revista Estomatología, 2004)
The main intention of these essay is to justify the professional audiophonologist participa-tion in holistic oral health team, especially on promotion of the helathy stomatoloy sistem and prevention activities oriented to encourage good craneofacial growt and oromotor develo-pment as well as to control oral unhealthy or injurius habits.